Better to send university students home - Abdullah, Muhammad Faris (Sun Media Corporation Sdn. Bhd., 2020)
BY April 14, the movement control order (MCO) will be a month old. That means university students, who had not gone home before the MCO, will also be restricted to their campuses for a month. In the absence of academic activities and restricted social activities, this would not be good for their state of mind.